Using trait-based approaches to study phytoplankton seasonal succession in a subtropical reservoir in arid central western Argentina - Beamud, Sara Guadalupe (2015)
The application of trait-based approaches has become a widely applied tool to analyse community assembly processes and dynamics in phytoplankton communities. Its advantages include summarizing information of many species without losing essentials of the main driving processes. Here, we used trait-based approaches to study phytoplankton temporal succession in a subtropical reservoir. We applied a combined approach including morphological traits (i.e. volume, surface) and functional clustering of species (morphology-based functional groups (MBFG) and Reynolds’ groups) and related the clustering of species with the environment. We found that this reservoir is characterized by a low richness and a bimodal distribution of phytoplankton biomass. Taxonomic and functional classifications were coincident, and the dominant species and groups biomasses were explained by the same group of variables. For instance, group X2, MBFG V and Carteria sp. biomasses were explained by: pH, Secchi disk depth, N-NH4; while group B, MBFG VI and Cyclotella ocellata biomasses were explained by stability of the water column, incident solar radiation, Secchi disk depth and N-NH4. From our results, we state that functional and taxonomic classifications are complementary rather than opposed approaches, and their specific uses depend exclusively on the aim of the study and the characteristics of the environment under evaluation. Our work is the first description of phytoplankton dynamics in a reservoir in the arid central western Argentina (Cuyo region).